THE ARRANGEMENTS OF COMPENSATION FOR MARINE POLLUTION BY PLASTIC WASTE IN INDONESIA - Fristikawati, Yanti; Fristikawati, I.B.R Supancana (Jurnal Paradigma Hukum Pembangunan, 2025)
One of the environmental damages currently quite disturbing is the ecological damage caused by plastic waste. Plastic waste is difficult to decompose so that it can disrupt the ecosystem of the land and the sea. One of the impacts of plastic waste is on the health of marine animals, where some of these animals, such as turtles, eat debris or plastic fragments. As a country with a large sea area, Indonesia must ensure its marine environment is not polluted by plastic waste. One way to prevent environmental damage is through regulation, where in addition to prevention, we must also look at what sanctions can be applied to those who violate the law by dumping rubbish in the sea. These can be criminal sanctions, such as fines and imprisonment, and sanctions to pay compensation, especially if victims are harmed. This research uses a normative legal method to answer the problem of how the rules in Indonesia regulate compensation in the event of pollution due to plastic waste. The current regulations are sufficient, but implementing compensation payments for plastic waste victims is still challenging.